Performing A* search for yard crane dispatching in container terminals - Guo, Xi (2011)
We address the problem of dispatching a yard crane in its appointed zone of a container terminal. The objective of yard crane dispatching is to determine a sequence for handling all coming jobs within the zone that minimizes the average vehicle waiting time. We propose 2 modified A* search algorithms with admissible heuristics to provide fast and optimal dispatching solution. Simulation results show that the algorithm using the improved heuristic is able to find the optimal solution over 2.4 times 1018 possible dispatching sequences in about 3 to 4 seconds under heavy work load.